Unlocking the role of silicon against biotic stress in plants - Verma, Krishan K.; Song, Xiu-Peng; Liang, Qiang; Huang, Hai-Rong; Bhatt, Rajan; Xu, Lin; Chen, Gan-Lin; Li, Yang-Rui (Frontiers in Plant Science, 2024)
The requirement for agricultural crops continues to enhance with the continuous growth of the human population globally. Plant pathogenic diseases outbreaks are enhancing and threatening food security and safety for the vulnerable in different regions worldwide. Silicon (Si) is considered a non-essential element for plant growth. It regulates the biological functions, plant development and productivity, and balance the defense mechanism in response to fungal, bacterial and pest attacks. The optimum crop yield can be achieved by applying Si in agricultural systems through different methods to replace or minimize the use of synthetic fertilizers. This approach can be effective on crop production during limited resources, extreme climates, pests and diseases, and environmental pollution. Silicon can be applied as foliar spray, priming of seeds, soil water irrigation, soil amendment and soilless medium (hydroponic) to enhance plant performance and stress tolerance capacity during stress conditions. This article summarized the effective roles of Si and the ability to perform in agroecosystems for better crop production, food security and safety for sustainable agriculture in the future.